The hymn to Dionysus : a novel - Pulley, Natasha (Bloomsbury, 2025)
"Raised in a Greek legion, Phaidros has been taught to follow his commander's orders at all costs. But when Phaidros rescues a baby from a fire at Thebes's palace, his commander's orders cease to make sense: Phaidros is forced to abandon the blue-eyed boy at a temple, and to keep the baby's existence a total secret. Years later, struggling with panic attacks and flashbacks, Phaidros is enlisted by the Queen to find her son, Thebes' young crown prince, who has vanished to escape an arranged marriage. The search leads him to a blue-eyed witch named Dionysus, whose guidance is as wise as the events that surround him are strange. In Dionysus's company, Phaidros witnesses sudden outbursts of riots and unrest, and everywhere Dionysus goes, rumors follow about a new god, one sired by Zeus but lost in a fire." --